Enteropatia crônica em cães na Serra Gaúcha - Casagrande, Giovanna Bergozza (My University, 2025)
Chronic enteropathies in dogs represent a heterogeneous group of long-standing gastrointestinal disorders, often challenging in both diagnosis and clinical management. The fecal score, a practical and non-invasive tool based on the visual assessment of stool characteristics, has been widely used to monitor intestinal health. This study aims to evaluate the applicability of the fecal scoring system as an auxiliary tool in the diagnosis of canine chronic enteropathies, discussing its correlation with clinical, laboratory, and histopathological findings. The systematic use of fecal scoring can provide objective data on treatment response, as well as assist in differentiating between various forms of enteropathy, such as food-responsive enteropathy, antibiotic-responsive enteropathy, and immunosuppressant-responsive enteropathy. The interpretation and analysis of the causative agent were carried out through phenotypic identification based on biochemical test results. From this, it becomes evident that, although the fecal score does not replace other diagnostic tests, its incorporation into clinical routine is recommended and can significantly contribute to the initial evaluation and better monitoring of the clinical progression of these patients. It was found that the presence of *E. coli* was significantly associated with the fecal score of the dogs (p < 0.001). [resumo fornecido pelo autor]
As enteropatias crônicas em cães representam um grupo heterogêneo de distúrbios gastrointestinais de longa duração, frequentemente desafiadores no diagnóstico e manejo clínico. O escore fecal, uma ferramenta prática e não invasiva baseada na avaliação visual das características das fezes, tem sido amplamente utilizado para monitorar a saúde intestinal. Este estudo tem como objetivo avaliar a aplicabilidade do escore fecal como instrumento auxiliar no diagnóstico das enteropatias crônicas caninas, discutindo sua correlação com achados clínicos, laboratoriais e histopatológicos. A utilização sistemática do escore fecal pode fornecer dados objetivos sobre a resposta ao tratamento, bem como auxiliar na diferenciação entre diferentes formas de enteropatias, como enteropatia responsiva à dieta, enteropatia responsiva a antibiótico e enteropatia responsiva a imunossupressor. A interpretação e análise do agente causador foi realizada através da identificação fenotípica a partir das provas bioquímicas encontradas. A partir disso, fica evidente que, mesmo que o escore fecal não substitua outros exames, sua incorporação à rotina clínica é indicada e pode contribuir significativamente para a avaliação inicial e um melhor acompanhamento da evolução clínica desses pacientes. Foi possível aferir que a presença de E. coli foi significativamente associada ao escore fecal dos cães (p < 0,001). [resumo fornecido pelo autor]
Keywords: Cães - Doenças; Intestinos - Doenças; Dogs - Diseases; Intestines - Diseases